2005
DOI: 10.1149/1.1845371
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cerium Conversion Coatings on AZ31 Magnesium Alloys

Abstract: Cerium conversion coatings, which have been used as protective coatings for aluminum alloys, are now being considered as an alternative to chromium conversion coatings for improving the corrosion resistance of magnesium alloys. This study investigated the evolution of conversion coatings on an AZ31 magnesium plate immersed in 0.05 M cerium nitrate solution. In addition to the expected growth of the conversion coating with immersion time, it was found that there may be an inherent adhesive weakness within the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 22 publications
3
75
1
Order By: Relevance
“…Our previous study showed that proton discharge accompanying oxidation and dissolution of magnesium substrate results in a pH rise ahead of the substrate/solution interface. 11) This high pH causes the precipitation of Mg 2þ and Al 3þ ions dissolved from the substrate as a magnesium/aluminum hydroxide layer directly contacting the substrate. Further away from the substrate/solution interface, the primary precipitation is Ce 3þ ions to cerium (III) hydroxide/oxide, since Mg 2þ and Al 3þ ions are markedly depleted due to their precipitation in the vicinity of the magnesium surface.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study showed that proton discharge accompanying oxidation and dissolution of magnesium substrate results in a pH rise ahead of the substrate/solution interface. 11) This high pH causes the precipitation of Mg 2þ and Al 3þ ions dissolved from the substrate as a magnesium/aluminum hydroxide layer directly contacting the substrate. Further away from the substrate/solution interface, the primary precipitation is Ce 3þ ions to cerium (III) hydroxide/oxide, since Mg 2þ and Al 3þ ions are markedly depleted due to their precipitation in the vicinity of the magnesium surface.…”
Section: Discussionmentioning
confidence: 99%
“…Accompanying these oxidation reactions, the primary reduction is proton discharge, which again leads to an increase in the pH ahead of the substrate/solution interface. 11,14) Ce 4þ then can precipitate as Ce(OH) 4 which, once dehydrated, transforms to cerium (IV) oxide (reaction 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations